Slow electron self-exchange in spite of a small inner-sphere reorganisation energy: the electron-transfer properties of a Copper complex with a Tetradentate Bispidine ligand - Comba, Peter; Kerscher, Marion; Roodt, Andreas (European journal of inorganic chemistry, 2004)
The electron self-exchange rate of [Cu(L)(OH2)]2+/1+, kexp11 (298.13 K) = 15 ± 11 m−1s−1 {L = dimethyl 3,7-dimethyl-9oxo-2,4-bis(2-pyridyl)-3,7-diazabicyclo[3.3.1]nonane-1,5-dicarboxylate}, was determined by a cross reaction. The analysis, based on classical Marcus theory, indicates that this relatively slow rate is to a large extent due to enthalpic terms (ΔG‡,exp11 = 62.8 ± 3.5 kJ·mol−1, ΔH‡,exp11 = 36.0 ± 2.7 kJ·mol−1 and ΔS‡,exp11 = −92 ± 10 J·mol−1K−1). The activation entropy is significant but not unusually large and the calculated outer-sphere reorganization energy, ΔG*,calcout = 20.5 kJ·mol−1, is at least of the same order of magnitude as the calculated inner-sphere reorganisation energy ΔG*,calcin = 18.6 kJ·mol−1, i.e. the deformation of the solvent sheath is a major reason for the slow electron transfer rate. This is believed to be due to the highly elastic coordination geometry which leads to little strain upon distortion enforced by the electron transfer but to comparably large structural changes and, hence, to a large outer-sphere reorganisation term.